(untitled) (CAHIERS MAGELLANES-NS, 2024)
Background: Early Post-Natal Care Services are defined as the care Given to the mother and the newborn baby after childbirth and the first few Weeks after. This time is the most life-threatening time since most maternal and neonatal mortality takes place. Method and material: A cross-sectional study was conducted, using a systematic random sampling technique. The study population within each PHC will involve all married women of childbearing age who are available at the time of the data collection and have delivered live babies during the last year and have agreed to participate. A questionnaire was developed with closed-ended questions filled through the researcher’s interviews with women who attended the PHCs. And it covers all the causes of the visits and the services that are provided to them. Result: The current study included 400 women who were surveyed for postnatal care visits. The average age of the study group was 27.5 ± 6.8 years. More than half of the included women did, not attend the postnatal care services, most women who attended the postnatal healthcare services (82.2%) had only one visit, and only 11 (5.6%) had three or more visits. Conclusion: Women's utilization of postnatal care services was relatively low, and the main determinants were the place of receiving antenatal care (especially PHCCs) in addition to women’s awareness about PNC services.